Establishment of modified IgA nephropathy rat model and assessment of oxidative stress - GAO Ming; ZHANG Lian-dong; ZHANG Li; WANG Chang; LU Yan (Linchuang shenzangbing zazhi)
Objective To modify the traditional Ig A nephropathy model and evaluate the oxidative stress status of the model,providing experimental evidence for the establishment of Ig A nephropathy animal model. Methods Twelve female SPF SD rats weighing 200-240 g were randomly divided into normal control group( group C) and modified model group( group M) according to the random digital table method. The animals in group C were gavaged with normal saline at 4 ml/kg and given subcutaneous injection at 0. 4 ml,and those in group M were treated with bovine serum albumin at 600 mg/kg every day by gavage,and subcutaneously injected with carbon tetrachloride at 0. 10 ml,castor oil at 0. 3 ml,thymosin at 3 mg and LPS at 0. 05 mg. At the 12 th week,the general states of rats in two groups were observed. Serum creatinine( SCr),blood urea nitrogen( BUN),albumin( Alb) and 24-h urine protein were determined. Ig A immunofluorescence,HE staining,biochemical index as well as the state of oxidative stress in the kidney were evaluated. Results All the rats in the group M suffered from mental depression,tiredness,decreased movement and sparse hair. BUN and SCr levels in group M were significantly higher( P < 0. 05),the level of Alb was significantly lower( P < 0. 01),and 24-h urine protein was significantly higher than those in group C( P < 0. 05). In group M,Ig A clumps were de-posited in the renal mesangial region,the glomerular mesangial area was slightly widened,even moderately broadened,and increased mesangial cells and matrix were observed by HE staining. The levels of SOD and T-AOC in renal tissue of group M were significantly lower( P < 0. 05),and the level of MDA was significantly higher than that of group C( P < 0. 05). Conclusions The modified Ig A nephropathy rat model is optimal,and the biochemical and pathological indexes are similar to those of human Ig A nephropathy. The change of oxidative stress in the kidney is one of the important pathological mechanisms involved in the process.